DELIBERATIVE LOCAL LEADERSHIP AS A MECHANISM FOR RELIGIOUS MODERATION: EVIDENCE FROM A MULTIRELIGIOUS VILLAGE - Akhsani Ulvatun Ni’mah; Titin Nurhidayati (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Religious diversity presents opportunities and challenges for social harmony, especially in multireligious rural communities. Existing studies tend to examine normative frameworks, state policies, and institutional approaches, leaving little attention to the practice of religious moderation at the grassroots level. This study fills this gap by analyzing village heads and Sapta Darma leaders who apply deliberative leadership and public governance mechanisms to religious issues. Using a qualitative case study approach, data were collected through in-depth interviews with village heads and religious leaders and supported by documentation from the village. The findings show that religious moderation in Sukoreno is achieved through deliberative leadership, as demonstrated by inclusive deliberation, continuous dialogue, and collaborative decision-making involving leaders from various communities. Deliberative leadership is further strengthened and made more effective through local practices such as njagong (informal communal interaction) and andhap asor (humility and respect). Village leadership also demonstrates inclusiveness by recognizing indigenous belief communities, including Sapto Darmo, as part of local religiosity. Differences in religious practices and celebrations are deliberated and mutually respected.